Young (<35 years) haploidentical versus old (≥35 years) mismatched unrelated donors and vice versa for allogeneic stem cell transplantation with post-transplant cyclophosphamide in patients with acute myeloid leukemia in first remission: a study on behalf of the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation - Nagler, Arnon; Labopin, Myriam; Swoboda, Ryszard; Blaise, Didier; Angelucci, Emanuele; Vydra, Jan; Corral, Lucía López; Bramanti, Stefania; Chiusolo, Patrizia; Kwon, Mi; Koc, Yener; Itäla-Remes, Maija; et al. (Bone marrow transplantation, 2024)
We compared transplantation (HSCT) outcomes in AML patients undergoing HSCT with post-transplant cyclophosphamide (PTCy) in first complete remission from 1065 young (<35 years) haploidentical (Haplo) donors (yHaplo) vs. 147 old (≥35 years) mismatched unrelated donors (oMMUD) (first comparison) and from 271 young (<35 years) MMUD (yMMUD) vs. 1315 old (≥35 years) Haplo donors (oHaplo) (second comparison). Acute graft-versus-host disease (aGVHD) grades II-IV were significantly lower in the yHaplo vs. oMMUD group (HR = 0.62, p = 0.007). There were no significant differences in chronic GVHD, non-relapse mortality (NRM), relapse incidence, leukemia-free survival, overall survival, and GVHD-free and relapse-free survival. As for the second comparison, more patients in the oHaplo group had de novo AML, 86.6% vs. 81.9% in the yMMUD group (p = 0.044), while myeloablative conditioning was used more frequently in the yMMUD group, 53.3% vs. 46.8% in the oHaplo group (p = 0.049). aGVHD grades II-IV and NRM were significantly lower in the yMMUD vs. oHaplo group (HR = 0.69, p = 0.013 and HR = 0.60, p = 0.022). All other transplant outcomes did not differ. In conclusion, HSCT from young alternative donors (<35 years) results in a lower incidence of grades II-IV aGVHD. In addition, NRM is lower in HSCT from yMMUD compared to HSCT from oHaplo.
Keywords: dospělí; Cyclophosphamide; Female; haploidentická transplantace; Europe; dítě; Age Factors; Adult; mladý dospělý; ženské pohlaví; přežití bez známek nemoci; Adolescent; věkové faktory; homologní transplantace; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; příprava pacienta k transplantaci; Evropa; Transplantation Conditioning; Middle Aged; Graft vs Host Disease; Remission Induction; Male; indukce remise; Unrelated Donors; Young Adult; nemoc štěpu proti hostiteli; akutní myeloidní leukemie; Transplantation, Homologous; Disease-Free Survival; lidé středního věku; Child; Transplantation, Haploidentical; mužské pohlaví; nepříbuzný dárce; cyklofosfamid; mladiství; Leukemia, Myeloid, Acute; Humans